Progress in 433 MHz RFQ technology at NPK LUTS NIIEFA - Svistunov, Yu.A.; Vorogushin, M.F.; Gavrish, Yu.N.; Budtov, A.A.; Bogdanov, P.V.; Ershov, V.A.; Grigoriev, V.I.; Liverovski, A.K.; Mudrolubov, V.G.; Petrov, V.I.; Silaev, S.A.; Strokach, A.P.; et al. (Вопросы атомной науки и техники, 2006)
The paper is a survey of progress in 433 MHz RFQ technology at Production Complex of Linacs and Cyclotrons
of D.V. Efremov Institute Sci. over past three years. RFQs and APF-cavities are designed as bases for ion accelerators
for different applications. The use of 433 MHz frequency determines high requirements for RFQ manufacture
facilities, which are discussed herein. The test experimental results of RFQ full-scale stands and high power rf testing
data under beam load of 1 MeV on a deuteron RFQ made of chromium copper are presented. Приведен обзор работ по созданию ПОКФ на 433 МГц в НПК ЛУЦ НИИЭФА им. Д.В. Ефремова за последние три года. ПОКФ и ПФФ-резонаторы планируется использовать в качестве основных резонаторов ускорителей ионов для различных применений. Использование частоты 433 МГц определяет высокие требования для изготовления ПОКФ, которые обсуждены в статье. Представлены экспериментальные результаты тестирования полномасштабных стендов ПОКФ и данные испытаний резонатора из хромистой меди для ускорения дейтронов до энергии 1 МэВ при высоком уровне ВЧ-мощности и нагрузке пучком. Наведено огляд робіт зі створення ПОКФ на 433 МГц у НПК ЛУЦ НІІЕФА ім. Д.В. Єфремова за останні
три роки. ПОКФ і ЗФФ-резонатори планується використати як основні резонатори прискорювачів іонів для
різних застосувань. Використання частоти 433 МГц визначає високі вимоги для виготовлення ПОКФ, які
обговорені в статті. Представлено експериментальні результати тестування повномасштабних стендів
ПОКФ і дані випробувань резонатора із хромистої міді для прискорення дейтронів до енергії 1 МеВ при
високому рівні ВЧ-потужності і навантаженню пучком.